Functionalized cork-polymer composites (CPC) by reactive extrusion using suberin and lignin from cork as coupling agents - Fernandes, Emanuel M.; Aroso, Ivo M.; Mano, João F.; Covas, José A.; Reis, Rui L. (Composites Part B: Engineering, 2014)
High density polyethylene (HDPE) and cork powder were compounded in a co-rotating twin-screw extruder to obtain cork-polymer composites (CPC) with improved properties. Benzoyl peroxide (BPO) was used as initiator agent, and suberin or lignin isolated from cork enhanced filler-matrix bonding and promoted mechanical reinforcement with environmental benefits. The novel composites were characterized in terms of dimensional stability, evolution of morphology, thermal and mechanical properties and their performance was compared with that of composites containing polyethylene-grafted maleic anhydride (PE-g-MA) as coupling agent. As expected, composites with coupling agent present higher mechanical properties, lower water uptake and thickness swelling variation. Suberin acts as plasticizer with antioxidant benefits, while lignin works as a coupling agent, improving tensile modulus and maximum strength. Increasing lignin content does not improve the mechanical properties but improves thermal stability.
Keywords: Coupling agent; Electron microscopy; Extrusion; Fibre/matrix bond; Polymer-matrix composites (PMCs)